Local Government Budget Allocation for the Socio-Economic Upliftment of Dalits, Women, and Marginalized in Nepal - Adhikari, Govinda (Journey for Sustainable Development and Peace Journal, 2026)
This study analyzes the inclusive provisions amidst exclusive practice in the context of local government budgeting in Nepal. The Constitution of Nepal (2015) mandates affirmative action for marginalized groups. This is reinforced by the Local Government Operation Act (2017) and related guidelines, including tools like LISA, which set an ideal benchmark of allocating at least 10% of local discretionary budgets for the socio-economic upliftment of Dalits, women, and other marginalized communities. The qualitative study employs document analysis of legal provisions, scholarly papers, and municipal budget review reports to evaluate the extent of inclusive budgeting in practice. Findings reveal a broad policy-implementation gap, with most local governments allocating fewer than 2% of their budgets to the marginalized. Elite capture persists, benefiting highly visible infrastructure schemes at the cost of social empowerment and rendering participation more tokenistic. Accountability arrangements remain absent, as functionary’s municipality budget constraints while diverting funds into politically opportune schemes. Without stronger enforcement, capacity-building, and transparent oversight, Nepal’s inclusive governance provisions risk remaining symbolic. This study provides valuable insights for policymakers, practitioners, and scholars committed to advancing equitable and effective local development.